Health anxiety and attentional bias toward virus‐related stimuli during the COVID‐19 pandemic (2020)
After the COVID-19 worldwide spread, evidence suggested a vast difusion of negative consequences on people’s mental health.Together with depression and sleep difculties, anxiety symptoms seem to be the most difused clinical outcome.The current contribution aimed to examine attentional bias for virus-related stimuli in people varying in their degree of health anxiety (HA). Consistent with previous literature, it was hypothesized that higher HA would predict attentional bias, tested using a visual dot-probe task, to virus-related stimuli. Participants were 132 Italian individuals that participated in the study during the lockdown phase in Italy. Results indicated that the HA level predicts attentional bias toward virus-related objects.This relationship is double mediated by the belief of contagion and by the consequences of contagion as assessed through a recent questionnaire developed to measure the fear for COVID-19.These fndings are discussed in the context of cognitive-behavioral conceptualizations of anxiety suggesting a risk for a loop efect. Future research directions are outlined.